IMPLEMENTING ADVERTISEMENT FOR IMPROVING STUDENTS’ UNDERSTANDING OF POLITENESS AND GENDER - Vina Fathira; Silvia Utami (English Review: Journal of English Education, 2019)
This research was based on students’ difficulties in understanding the concept of politeness and gender. Advertisement can be one of the alternative techniques to improve students’ understanding on the concept of politeness and gender. This study aims at improving students’ understanding of politeness and gender and finding the factors influencing the improvement. This Classroom Action Research involved ten third-year-students at STIBA Persada Bunda Pekanbaru. The data collection techniques used were tests, fieldnotes, observation, and interview. The results showed that students’ understanding of politeness and gender significantly improved after applying advertisements in the teaching and learning process in which the students’ understanding which were at the low level category increases to the good level category. Some factors affecting the students’ improvement were students’ active participation in obtaining information and students’ enthusiasm during the learning process. In conclusion, the implementation of advertisements can improve students’ understanding of politeness and gender concepts.